2003
DOI: 10.1007/s10103-002-0235-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on surface roughness and microleakage test in cavities prepared by Er:YAG laser irradiation and etched bur cavities

Abstract: The purposes of this study were to investigate the surface morphology, suface roughness of cavities prepared by Er:YAG laser irradiation, and compared the microleakage degree after composite resin restoration with etched bur cavities, in vitro. In each of the 30 human extracted teeth, two shallow cavities were prepared; one prepared with the Er:YAG laser system on the buccal surface, and one produced on the lingual (palatal) surface with a high-speed turbine. Five cavities from each group were investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 12 publications
5
44
0
3
Order By: Relevance
“…26 In cavities that were conventionally prepared, etching with phosphoric acid resulted in removal of smear layer and exposure of enamel prism sheaths and dentinal tubules. 27 In this study, microleakage was seen to be higher following conventional etching. This is probably because there are no definite etching patterns seen in primary teeth.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…26 In cavities that were conventionally prepared, etching with phosphoric acid resulted in removal of smear layer and exposure of enamel prism sheaths and dentinal tubules. 27 In this study, microleakage was seen to be higher following conventional etching. This is probably because there are no definite etching patterns seen in primary teeth.…”
Section: Discussionmentioning
confidence: 65%
“…7 The highly irregular surfaces following laser treatment results in loss of smear layer, intact enamel rods and opening of dentinal tubules. 15,27 In the absence of a smear layer, there can be improved adhesion due to better penetration of both primer and adhesive. 3,13,27 Howev- er, Bertrand et al reported of better marginal adaptation of restorations in permanent teeth, when Er:YAG laser preparation was followed by total acid etching.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the effects of erbium laser and diamond bur preparation on microleakage 14,15,29,[52][53][54][55] . Some studies found that laser irradiation exhibited same or even better microleakage outcome than did the conventional bur method [53][54][55] , but other studies had contradictory results 29,52) . During cavity preparation with burs, the inevitable noise, vibration, pressure, and heat caused by high-speed drilling inevitably brings much discomfort and displeasure to the patient 56,57) .…”
Section: Discussionmentioning
confidence: 99%
“…31 In another study, cavities prepared by Er:YAG laser were found to be capable of decreasing the microleakage of resin composite restorations, and their efficiency was similar to etched bur cavities. 32 Moldes and others 33 compared the degree of microleakage of composite restorations performed by lasers and those by conventional drills associated with two adhesive systems. The enamel margins demonstrated no differences in microleakage for all treatments.…”
Section: Discussionmentioning
confidence: 99%